123k views
4 votes
Logarithms- How to answer these questions?

Logarithms- How to answer these questions?-example-1
User Frank Ibem
by
5.9k points

2 Answers

5 votes

Answer:

For #3:
\log_px=-4

Explanation:

I'm a little rusty on my logarithm rules for #2, but here's an explanation of #3.

Logarithms: the Inverse of Exponents

In a sense, we can think of operations like subtraction and division as different ways of representing addition and multiplication. For instance, the same relationship described by the equation 2 + 3 = 5 is captured in the equation 5 - 3 = 2, and 5 × 2 = 10 can be restated as 10 ÷ 2 = 5 without any loss of meaning.

Logarithms do the same thing for exponents: the expression
2^3=8 can be expressed in logarithms as
\log_28=3. Put another way, logarithms are a sort of way of pulling an exponent out onto its own side of the equals sign.

The Problem

Our problem gives us two facts to start: that
log_p(x^2y^3)=7 and
p^5=y. With that, we're expected to find the value of
\log_px.
p^5=y stands out as the odd-equation-out here; it's the only one not in terms of logarithms. We can fix that by rewriting it as the equivalent statement
log_py=5. Now, let's unpack that first logarithm.

Justifying Some Logarithm Rules

For a refresher, let's talk about some of the rules logarithms follow and why they follow them:

Product Rule:
\log_b(MN)=\log_bM+\log_bN

The product rule turns multiplication in the argument (parentheses) of a logarithm into addition. For a proof of this, consider two numbers
M=b^x and
N=b^y. We could rewrite these two equations with logarithms as
\log_bM=x and
\log_bN=y. With those in mind, we could say the following:


  • \log_b(MN)=\log_b(b^xb^y) (Substitution)

  • \log_b(b^xb^y)=log_b(b^(x+y)) (Laws of exponents)

  • \log_b(b^(x+y))=x+y (
    \log_b(b^n)=n)

  • x+y=\log_bM+\log_bN (Substitution)

And we have our proof.

Exponent Rule:
\log_b(M^n)=n\log_bM

Since exponents can be thought of as abbreviations for repeated multiplication, we can rewrite
\log_b(M^n) as
\log_b(M* M\cdots * M), where M is being multiplied by itself n times. From there, we can use the product rule to rewrite our logarithm as the sum
\log_bM+\log_bM+\cdots+\log_bM, and since we have the term
\log_bM added n times, we can rewrite is as
n\log_bM, proving the rule.

Solving the Problem

With those rules in hand, we're ready to solve the problem. Looking at the equation
\log_p(x^2y^3)=7, we can use the product rule to split the logarithm into the sum
\log_p(x^2)+\log_p(y^3)=7, and then use the product rule to turn the exponents in each logarithm's argument into coefficients, giving the equation
2\log_px+3\log_py=7.

Remember how earlier we rewrote
p^5=y as
log_py=5? We can now use that fact to substitute 5 in for
log_py, giving us


2\log_px+3(5)=7

From here, we can simply solve the equation for
\log_px:


2\log_px+15=7\\2\log_px=-8\\\\\log_px=-4

User Lane Aasen
by
6.4k points
7 votes

Answer:

2. m = b³ (= 216)

3. logp(x) = -4

Explanation:

2. The given equation can be written using the change of base formula as ...

... log(m)/log(b) + 9·log(b)/log(m) = 6

If we define x = log(m)/log(b), then this becomes ...

... x + 9/x = 6

Subtracting 6 and multiplying by x gives ...

... x² -6x +9 = 0

... (x -3)² = 0 . . . . . factored

... x = 3 . . . . . . . . . value of x that makes it true

Remembering that x = log(m)/log(b), this means

... 3 = log(m)/log(b)

... 3·log(b) = log(m) . . . . . multiply by the denominator; next, take the antilog

... m = b³ . . . . . . the expression you're looking for

___

3. Substituting the given expression for y, the equation becomes ...

... logp(x^2·(p^5)^3) = 7

... logp(x^2) + logp(p^15) = 7 . . . . . use the rule for log of a product

... 2logp(x) + 15 = 7 . . . . . . . . . . . . . use the definition of a logarithm

... 2logp(x) = -8 . . . . . . . . . . . . . . . . subtract 15

... logp(x) = -4 . . . . . . divide by 2

User Enessa
by
5.7k points